Gender and age differences in the sleep habits : a cross-sectional study in adolescents - Amaral, Odete (2016)
Objectives: Analyze gender and age differences in sleep habits in a sample of adolescents. Design: A cross-sectional study. Setting: Public schools of Viseu, Portugal. Participants: Sample consisted of 7534 students, aged 11-20 years (mean age: 14.96 ± 1.81 years; 53.6% girls). Measurements: Data was collected using a self-administered questionnaire, answered in class and consists of questions to assess insomnia (DSM-IV criteria), sleep patterns, socio-demographic and daily habit variables. Results: Mean sleep duration in this sample was 8.02 ± 1.13 h. Age interfered with sleep duration that decreased with the increasing of age, from 8.45 ± 1.14 h among 11/12 years old to 7.37 ± 1.04 h for ages ≥ 17 years old. Insomnia and symptoms of insomnia were associated with gender and with increasing of age. Nearly 80% of students reported daytime tiredness, 66.7% sleepiness during the day; 56.1% during classes and 47.6% reported waking up with headaches, all variables more prevalent among girls and older adolescents. Conclusions: The sleep problems and variables related to sleep have become more frequent among girls and with increasing age. We recommend that the promotion of sleep hygiene and prevention of the consequences should be encouraged in adolescents and their families, especially among the female gender and older adolescents.